Using zircon U-Pb ages and trace element chemistry to constrain the timing of metamorphic events, pegmatite dike emplacement, and shearing in the southern Parry Sound domain, Grenville Province, Canada - Marsh, J; Gerbi, Chris; Culshaw, N; Johnson, Se; Wooden, Joseph; Clark, Chris (Elsevier BV, 2012)
The integration of zircon U–Pb ages and trace element chemistry with structural and petrologic relations from a range of sample types provides important temporal constraints on the tectono-metamorphic evolution of the southern Parry Sound domain (PSD), Ontario, Canada, and the processes attending development of the underlying Twelve Mile Bay shear zone (TMBSZ). Intact granulites preserve ca. 1145 Ma ages, slightly younger than those farther to the north in the interior PSD, but similar to that of the underlying granulite-to-amphibolite facies Parry Sound shear zone. Weaker zircon HREE enrichment in sheared and retrogressed samples with partially resorbed garnet porphyroblasts (containing abundant zircon inclusions) suggests that the 1128–1143 Ma ages common to sheared rocks in the southern PSD record an earlier phase of metamorphism and deformation, and not the timing of shear zone development. Deformed pegmatite dikes bounded by sheared and retrogressed wall rocks from across the southern interior PSD consistently record ca. 1100 Ma ages, indicating synchronous pegmatite emplacement across the transect and constraining the bounding amphibolite-facies shear zones to ≤1100 Ma. TMBSZ samples retain evidence for (1) the older (ca. 1145 Ma) high-grade metamorphic event, (2) pegmatite emplacement and shear deformation at ca. 1100 Ma, and (3) a later (ca. 1070 Ma) shearing event. Combined with published structural and petrologic data, these ages indicate that pegmatite emplacement and shearing in the TMBSZ was synchronous with that in the southern interior PSD; further confirming published models for TMBSZ development. Additionally, the data suggest that the Twelve Mile Bay assemblage (within the TMBSZ) experienced high-grade metamorphism synchronously with the interior PSD, and may therefore be correlative with the basal PSD to the north.